A case of a modelled saturation level for cooperative flight departures. (2018) - Schefers, Nina; González, Juan José Ramos; Nosedal, Jenaro
Owing to increasing air traffic operations, the development of advanced decision support tools (DSTs) in air traffic management (ATM) is driven forward to guarantee that sustainable transport logistics balance airspace capacity with user demands. In this paper, the tuning of calculated-take-off times (CTOTs) as a tool for mitigating the propagation of perturbations between trajectories in dense sectors is analysed. The proposed methodology uses a powerful tool for predicting potential spatio-temporal concurrence events between trajectories over the European airspace. In the first place, the aim is to remove the detected concurrence events by considering bounded time stamp adjustments on strategic agreed points of the aircraft trajectory. In the second place, the model is extended to identify route interdependencies of over constraint topologies that could lead to a saturation event. The approach is based on a robust constraint programming model aiming to determine the feasible time stamp changes considering reference based trajectories (RBTs).